Structural basis for ligand recognition and activation of the prostanoid receptors - Xiu Li; Xuan Zhang; Xin Wen; Daolai Zhang; Changxiu Qu; Xinyi Miao; Wenkai Zhang; Ru Zhang; Guibing Liu; Peng Xiao; Jin-Peng Sun; Weimin Gong (Cell Reports, 2024)
Summary: Prostaglandin F2α (PGF2α) and thromboxane A2 (TXA2) are endogenous arachidonic acid metabolites, modulating diverse physiological processes including inflammation and cardiovascular homeostasis through activating PGF2α receptor (FP) and TXA2 receptor (TP). Ligands targeting FP and TP have demonstrated efficacy in treating conditions like glaucoma and cardiovascular diseases in humans, as well as reproductive-related diseases in animals. Here, we present five cryoelectron microscopy structures illustrating FP and TP in complex with Gq and bound to PGF2α (endogenous ligand), latanoprost acid (a clinical drug), and two other synthetic agonists. Combined with mutational and functional studies, these structures reveal not only structural features for the specific recognition of endogenous ligands and attainment of receptor selectivity of FP and TP but also the common mechanisms of receptor activation and Gq protein coupling. The findings may enrich our knowledge of ligand recognition and signal transduction of the prostanoid receptor family and facilitate rational ligand design toward these two receptors.